2021
DOI: 10.4155/fmc-2021-0036
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibitors of Carboxylesterase Notum

Abstract: Notum has recently been identified as a negative regulator of Wnt signaling through the removal of an essential palmitoleate group from Wnt proteins. There are emerging reports that Notum plays a role in human disease, with published data suggesting that targeting Notum could represent a new therapeutic approach for treating cancer, osteoporosis and neurodegenerative disorders. Complementary hit-finding strategies have been applied with successful approaches that include high-throughput screening, activity-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 46 publications
(63 reference statements)
0
31
0
Order By: Relevance
“…Notum also plays a key role in adult brain ventricular–subventricular zone neurogenesis . Notum inhibitors can rejuvenate aged colon stem cells, increase cortical bone thickness and strength, and increase adult neuronal progenitors and are being investigated for potential treatment of neurodegenerative pathologies such as Alzheimer’s disease, in which Wnt signaling is commonly downregulated. , More recently, Notum has been identified as a key mediator for adenomatous polyposis coli (Apc)-mutated tumor cell fixation and tumor formation, while Notum inhibitors abrogate the ability of Apc-mutant cells to expand . These pieces of evidence highlight the importance of Notum as a novel target for drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…Notum also plays a key role in adult brain ventricular–subventricular zone neurogenesis . Notum inhibitors can rejuvenate aged colon stem cells, increase cortical bone thickness and strength, and increase adult neuronal progenitors and are being investigated for potential treatment of neurodegenerative pathologies such as Alzheimer’s disease, in which Wnt signaling is commonly downregulated. , More recently, Notum has been identified as a key mediator for adenomatous polyposis coli (Apc)-mutated tumor cell fixation and tumor formation, while Notum inhibitors abrogate the ability of Apc-mutant cells to expand . These pieces of evidence highlight the importance of Notum as a novel target for drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…An original finding of the present study is that TTFields cause a marked upregulation of NOTUM gene. Although the function of NOTUM gene is not fully elucidated yet, it has been reported that it is a negative regulator of Wnt signaling [ 25 ]. Since the deregulation of Wnt pathway plays an important role not only in the development of many different tumors, but also to the resistance of cancer cells to anticancer drugs [ 26 28 ], the upregulation of NOTUM by TTFields might have a therapeutic effect against resistant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The key tools to enable this progress are fit-for-purpose small-molecule inhibitors of Notum carboxylesterase activity. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%